THE ROLE OF THE STATE IN THE DEVELOPMENT OF TOURISM IN UZBEKISTAN (Marketing Journal, 2025)
The article examines Uzbekistan’s tourism development with a focus on the Zomin ecotourism zone. It analyzes recent reforms, infrastructure improvements, and policy measures aimed at increasing tourist inflow and economic diversification. The study applies SWOT and trend analysis to assess achievements and challenges, proposing recommendations to enhance tourism sustainability and competitiveness.
Keywords: changes in the field of tourism; decrees and decisions of the president; the integral connection of tourism with the economy; and work plans focused on the field of tourism in the territory of the Republic of Uzbekistan